2015
DOI: 10.1038/nnano.2015.37
|View full text |Cite|
|
Sign up to set email alerts
|

Water desalination using nanoporous single-layer graphene

Abstract: By creating nanoscale pores in a layer of graphene, it could be used as an effective separation membrane due to its chemical and mechanical stability, its flexibility and, most importantly, its one-atom thickness. Theoretical studies have indicated that the performance of such membranes should be superior to state-of-the-art polymer-based filtration membranes, and experimental studies have recently begun to explore their potential. Here, we show that single-layer porous graphene can be used as a desalination m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
1,103
3
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,514 publications
(1,125 citation statements)
references
References 41 publications
11
1,103
3
8
Order By: Relevance
“…As a comparison, the pore density of the nanoporous graphene membrane recently achieved experimentally by Surwade et al is estimated to be ~10 12 pores per cm 2 . 11 In addition, our calculations predict that the CTF--1 membrane is able to reject salt at a rate of 91%, which provides opportunities in brackish water desalination or multi--stage sea water desalination. This salt rejection rate, however, is not high enough to meet the requirements of widely used one--step sea water RO processes (i.e., ~99% is needed), indicating the membrane's pore is still marginally too large.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…As a comparison, the pore density of the nanoporous graphene membrane recently achieved experimentally by Surwade et al is estimated to be ~10 12 pores per cm 2 . 11 In addition, our calculations predict that the CTF--1 membrane is able to reject salt at a rate of 91%, which provides opportunities in brackish water desalination or multi--stage sea water desalination. This salt rejection rate, however, is not high enough to meet the requirements of widely used one--step sea water RO processes (i.e., ~99% is needed), indicating the membrane's pore is still marginally too large.…”
mentioning
confidence: 81%
“…10 Moreover, recent work of Surwade et al has further experimentally realized such single--layered nanoporous graphene membranes and demonstrated their potential in desalination at the lab scale. 11 However, the production of nanoporous graphene membranes with perfectly sized nanopores still remains a great challenge. Moreover, to allow unprecedentedly high water fluxes, it is of great importance to achieve a pore density as high as possible while preventing pores from overlapping, a goal best achieved with a well--ordered pore structure.…”
mentioning
confidence: 99%
“…8d). Considerable energy could also be generated by exploiting parallelization, with multiple small pores or even a continuous porous structure within a large area of single-layer MoS 2 membrane 26 , which could be scaled up for mass production using the ECR pore-fabrication technique 16 or plasma-based defect creation 27 .…”
Section: Letter Researchmentioning
confidence: 99%
“…8d). Considerable energy could also be generated by exploiting parallelization, with multiple small pores or even a continuous porous structure within a large area of single-layer MoS 2 membrane 26 , which could be scaled up for mass production using the ECR pore-fabrication technique 16 or plasma-based defect creation 27 .The use of individual nanopores as a micro/nano power source has long been expected 22 . We find here that an individual osmotic generator can also serve as a nanopower source for a self-powered nanosystem, owing to its high efficiency and power density.…”
mentioning
confidence: 99%
“…Reporting in this issue of Nature Nanotechnology, Ivan Vlassiouk, Shannon Mahurin and colleagues have now shown that a single layer of nanoporous graphene can be used to desalinate water 10 . The pores are created in the graphene layer by exposing the material to short bursts of oxygen plasma, a process that allows holes of precise dimensions to be controllably etched in the layer.…”
Section: Editorialmentioning
confidence: 99%